Static and Dynamic Properties of Elemental Liquid Pd: An Orbital Free Molecular Dynamic Study - Molla, M. R.; Ziauddin Ahmed, A. Z.; Bhuiyan, G. M. (Journal of Nepal Physical Society, 2020)
We have studied the static and dynamic properties of liquid metal, namely Pd at thermodynamic state T=1853K within the scope of the orbital free ab-initio molecular dynamics (OF-AIMD) simulation technique. In this simulation process, electronic energy is calculated by using the Hohenberg-Kohn version of DFT. Here the electron-ion interaction energy functional is approximated by a local pseudopotential prescribed by Bhuiyan et al. The local density approximation is used to describe the exchange-correlation energy functional. The static structure factor, S(q), pair distribution function, g(r), coordination number, Nc, and isothermal compressibility, κT, are studied which are familiar as static properties. The single particle and collective dynamics namely diffusion coefficient, dynamic structure factor, velocity of sound, shear viscosity etc. are also studied. The results of calculation agree well with experimental as well as other theoretical values.